Banana splits and policy challenges: The ACP Caribbean and the fragmentation of interest coalitions - Clegg, Peter (European Review of Latin American and Caribbean Studies, 2005)
The article considers the changes that have taken  place within the political economy of international  trade over the last decade. The work begins by  assessing briefly the dynamics of the last successful trade negotiations undertaken by the ACP Caribbean – the agreement on a single European  banana market in 1993. Since then, however, the  international political and economic climate has  dramatically changed. The article evaluates recent  developments, which have highlighted attention  on the political acceptability of trade discrimination, particularly within the context of the General  Agreement on Tariffs and Trade and the World Trade Organisation. In addition, there is an analysis of the reform process undertaken by the European Union, both in terms of its membership and  policy agenda, which has seriously impacted on  Caribbean economic interests. The article establishes that the actors representing the Caribbean  were extremely successful in constructing strategic coalitions to defend their trading interests in  the early 1990s, but the region must now appreciate that the international environment has changed  so dramatically that former negotiating strategies  are no longer appropriate. An awareness of the  changed negotiating environment on the part of  the Caribbean is vitally important if ongoing  international trade negotiations are to be completed to the region’s satisfaction. Resumen: Batallas bananeras y desafíos políticos:  El grupo ACP del Caribe y la fragmentación de las coaliciones de interésEste trabajo considera los cambios ocurridos en la  economía política del comercio internacional  durante la última década. El artículo comienza  con una breve evaluación de la dinámica de las  últimas negociaciones comerciales satisfactorias  del grupo ACP del Caribe: el acuerdo sobre un  mercado único bananero europeo en 1993. Desde  entonces, sin embargo, el clima político y  económico internacional ha cambiado drásticamente. El artículo evalúa los recientes acontecimientos que han puesto de relieve la aceptabilidad política de la discriminación comercial, en  particular en el contexto del Acuerdo General sobre Tarifas y Comercio y la Organización Mundial del Comercio. Además, se hace un análisis  del proceso de reforma efectuado por la Unión  Europea, tanto en términos de su ampliación  como de su agenda política, los cuales han tenido  un grave impacto en los intereses económicos  caribeños. El artículo establece que a principios de los años 90 los representantes caribeños tuvieron gran éxito a la hora de desarrollar estrategias para defender sus intereses comerciales, pero  en estos momentos la región debe tomar nota de  que el ambiente internacional ha cambiado de  forma tan radical que las antiguas estrategias de  negociación no pueden considerarse ya como  apropiadas. Para que la región pueda asegurar un  resultado positivo de las actuales negociaciones,  es de vital importancia que el Caribe tome conciencia del nuevo clima en que se desarrollan dichas negociaciones.